2022
DOI: 10.1111/sode.12633
|View full text |Cite
|
Sign up to set email alerts
|

Parenting is genetically influenced: What does that mean for research into child and adolescent social development?

Abstract: Individual differences in child and adolescent social development are due to a combination of variation in genetic propensity and environmental conditions. That is, variation in social domains like bullying-victimization, loneliness and pro-and antisocial behaviour is genetically influenced to a substantial extent. That is not to say that social contexts also do not play an important role in shaping social development. Indeed, parenting and parent-child relationship quality have been associated with various as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 110 publications
0
6
0
1
Order By: Relevance
“…Whatever the twin zygosity, parents gave rather similar responses to the absurd Wildman items, which suggested a substantial common influence. Because of the child-based instead of parent-based twin design (Kretschmer, 2023) common influences we found despite diverging environments that DZ twin children create for their parents represent parents’ own characteristics which are potentially influenced by their genotypes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Whatever the twin zygosity, parents gave rather similar responses to the absurd Wildman items, which suggested a substantial common influence. Because of the child-based instead of parent-based twin design (Kretschmer, 2023) common influences we found despite diverging environments that DZ twin children create for their parents represent parents’ own characteristics which are potentially influenced by their genotypes.…”
Section: Discussionmentioning
confidence: 90%
“…For almost all variables, an AE model provided the best fit, and goodness of fit indices can be found in Table S4 in the online supplemental materials. In the parents, a CE model provided the best fit for their responses to the Wildman questions, however, note that these estimates are computed in a child-based twin design (Kretschmer, 2023) in which the effects of parent's genetic makeup are represented in estimates of the C component in the ACE model. Heritability of the child-reported Wildman score was 44%.…”
Section: Twin Modelsmentioning
confidence: 99%
“…One agenda for future initiatives should thus elaborate on this positive association by exploring additional dispositional moderators (e.g., sympathy; Xu & Zhang, 2023 ; grit; Lan et al, 2019 ) to discuss the unexplained variance found in the present studies. A third limitation that needs to be mentioned is that genetic factors might present a potential confound in the current findings because autonomy-supportive parents might transfer genetic dispositions associated with prosocial behavior to their children (Kretschmer, 2023 ). Future studies might use a genetically informed design to disentangle potential genetic and environmental processes that explain these study associations.…”
Section: Discussionmentioning
confidence: 99%
“…nscr collega's Camiel van der Laan en Steve van de Weijer [24] onderzochten met data van het Neder lands Tweeling Register de directe en indirecte effecten op normoverschrijdend gedrag en concludeerden dat genetische factoren een belangrijke rol spelen in het verklaren van de clustering van agressie in bepaalde families. Gronings onder zoek van Tina Kretschmer, Charlotte Vrijen en collega's naar de interactie tussen genetische aanleg voor externalizerend probleemgedrag van kinderen en omgevingsfactoren zoals opvoeding en gezinsfuntioneren laat zien hoe complex de rela tie tussen aanleg, het tot uiting komen van gedrag, en omge ving eigenlijk is [22].…”
Section: Intergenerationele (Dis)continuïteitunclassified